A 0.3–6 ​GHz noise and distortion cancelling LNA achieving an NF of 2.8±0.3 ​dB in 0.18-μm SiGe BiCMOS process. (November 2020) - Li, Zhenrong; Duan, Yiming; Li, Zhen; Wang, Zeyuan; Zhuang, Yiqi
Abstract: This paper presents a noise and distortion cancelling wideband low-noise amplifier (LNA) in JAZZ 0.18- μ m SiGe BiCMOS process. In the proposed design, a shunt feedback (SFB) and a common-emitter (CE) paths are adopted to reduce the dominant noise contribution of the main path. To enhance the linearity, the derivative superposition method is modified to eliminate the whole nonlinearity components. Moreover, with the help of an n-type MOS acted as a resistive load of the CE path, both flat gain and acceptable output impedance matching are achieved. The measurement results exhibit that the LNA has an input third-order intercept point (IIP3 ) of −4 dBm with a noise figure (NF) of 2.8 ​± ​0.3 ​dB and a power gain 16.5 ​± ​0.2 ​dB from 0.3 to 6 ​GHz. The circuit draws 14.5 ​mA dc current from a 3.3 ​V supply for core area of 0.22 ​mm 2 .